Congregation for the Evangelization of Peoples: Four Hundred Years in the Service of the Missionary World - Rostkowski, Marek Adam (International bulletin of mission research, 2022)
The Congregation for the Evangelization of Peoples, commonly called Propaganda Fide, turned four hundred years old on January 6, 2022. Here we try to answer three fundamental questions about the Congregation: Why? For what purpose? Has it succeeded in reaching its objectives? We present here only the highlights of the history and activity of this organ of the Holy See in the service of the missionary world, including its coordination of the work of evangelization, missionary formation, and missionary cooperation.